Principles of state environmental control and their classification. (Journal of actual problems of jurisprudence, 2016)
Principles of environmental control in the sphere of environmental protection can be classified into general and special,and special on principles of environmental control and principles of public authorities. The author defines the principles of environmental control, open concept and content, gives their classification.
Keywords: principles; environmental control; environmental principles